Exploring the influencing factors of patients sending red packets and the necessity of doctor-patient red packet agreements - Li, Pingli; Wu, Lixiang; Zhang, Jie; Xiang, Surong; Fang, Li (Frontiers in Public Health, 2025)
ObjectiveTo investigate the influencing factors of inpatients giving red packets to doctors and explore the necessity of doctor-patient red packet agreements.MethodsA questionnaire survey was conducted among inpatients and their families who were hospitalized in several hospitals in Chengdu from January to June 2023. The survey asked about the patients’ (or their families’) attitudes and opinions on whether it was necessary to give red packets to doctors during hospitalization.ResultsThe vast majority of patients (80.7%) thought that it was not necessary to give red packets to doctors, and 87.0% of patients had never given red packets. 59.7% of patients chose senior doctors as the recipients of red packets, and 90.0% of patients thought that it was necessary to give red packets to doctors in 3A-grade hospitals. Patients’ attitudes toward giving red packets were positively influenced by their education level and previous experience of giving red packets.ConclusionDespite education level and previous experience of giving red packets were all positive influencing factors for patients giving red packets, the proportion of patients who had given or intended to give red packets was relatively low. The majority of patients believed that giving red packets was unnecessary, and they held the view that doctors would not treat them less actively if they did not receive red packets. The question of whether signing a red packet agreement is necessary is worth contemplating at this time.